Phytochrome-Dependent Regulation of ZFP6 and ZFPH Impacts Photomorphogenesis in Arabidopsis thaliana - Cota-Ruiz, Keni; Oh, Sookyung; Montgomery, Beronda L. (Frontiers in Plant Science, 2022)
Phytochromes (phy) are key regulators of photomorphogenesis in plants. Among the different phys characterized in higher plants (i.e., phyA to phyE), phyA and phyB primarily regulate phenotypic responses in plants under far-red (FR) and red (R) conditions, respectively. Recent findings suggest that some zinc finger proteins (ZFPs) are involved in plant light-modulated morphogenesis. However, the interaction(s) between phyA, phyB and ZFP homologs potentially involved in photomorphogenesis, as well as their phenotypic and molecular effects in Arabidopsis seedlings exposed to R and FR light remain to be elucidated fully. Prior analyses with phytochrome chromophore deficient lines indicated that ZFP6 expression is misregulated compared to levels inCol-0 wild type (WT). Here, we used plants with phytochrome chromophore or apoprotein (specifically phyA and phyB) deficiencies, lines with mutations in ZFP6 and ZFP6 HOMOLOG (ZFPH) genes, and plants overexpressing ZFP6 to examine regulatory interactions between phytochromes, ZFP6, and ZFPH. Our results indicate that phytochromes are required for downregulation of ZFP6 and ZFPH and suggest a role for light-regulated control of ZFP levels in phytochrome-dependent photomorphogenesis. Conversely, PHYB is downregulated in zfp6 mutants under R light. Analyses of a zfp6zfph double mutant confirmed disruption in photomorphogenic phenotypes, including the regulation of hypocotyl elongation in seedlings grown under FR light. In addition, PIF3 and PIF4 levels are transcriptionally regulated by ZFP6 and ZFPH in a gibberellic acid-dependent manner. ZFP6 overexpression resulted in opposite phenotypic responses to those observed in the zfp6 and zfph mutants grown in FR and R light, as well as a reduction in the rosette size of mature ZFP6 OX plants relative to WT under white light. Based on these observations, we provide insight into how phy and ZFPs interact to regulate specific aspects of light-dependent processes in Arabidopsis.